The effects of multiple-joint isokinetic resistance training on maximal isokinetic and dynamic muscle strength and local muscular endurance - Ratamess, N. A.; Beller, N. A.; Gonzalez, A. M.; Spatz, G. E.; Hoffman, J. R.; Ross, R. E.; Faigenbaum, A. D.; Kang, J. (Journal of Sports Science & Medicine, 2016)
The transfer of training effects of multiple-joint isokinetic resistance training to dynamic exercise performance remain poorly understood. Thus, the purpose of the present study was to investigate the magnitude of isokinetic and dynamic one repetition-maximum (1RM) strength and local muscular endurance increases after 6 weeks of multiple-joint isokinetic resistance training. Seventeen women were randomly assigned to either an isokinetic resistance training group (IRT) or a non-exercising control group (CTL). The IRT group underwent 6 weeks of training (2 days per week) consisting of 5 sets of 6-10 repetitions at 75-85% of subjects' peak strength for the isokinetic chest press and seated row exercises at an average linear velocity of 0.15 m s(-1) [3-sec concentric (CON) and 3-sec eccentric (ECC) phases]. Peak CON and ECC force during the chest press and row, 1RM bench press and bent-over row, and maximum number of modified push-ups were assessed pre and post training. A 2 x 2 analysis of variance with repeated measures and Tukey's post hoc tests were used for data analysis. The results showed that 1RM bench press (from 38.6 ± 6.7 to 43.0 ± 5.9 kg), 1RM bent-over row (from 40.4 ± 7.7 to 45.5 ± 7.5 kg), and the maximal number of modified push-ups (from 39.5 ± 13.6 to 55.3 ± 13.1 repetitions) increased significantly only in the IRT group. Peak isokinetic CON and ECC force in the chest press and row significantly increased in the IRT group. No differences were shown in the CTL group for any measure. These data indicate 6 weeks of multiple-joint isokinetic resistance training increases dynamic muscle strength and local muscular endurance performance in addition to specific isokinetic strength gains in women. Key pointsMultiple-joint isokinetic resistance training increases dynamic maximal muscular strength, local muscular endurance, and maximal isokinetic strength in women.Multiple-joint isokinetic resistance training increased 1RM strength in the bench press (by 10.2%), bent-over barbell row (by 11.2%), and maximal modified push-up performance (by 28.6%) indicating a carryover of training effects to dynamic exercise performance.The carryover effects may be attractive to strength training and conditioning professionals seeking to include alternative modalities such as multiple-joint isokinetic dynamometers to resistance training programs.